Anti-methanogenic effect of phytogenic extract of Moringa oleifera on methane mitigation through inhibition of methyl-coenzyme M reductase receptor: In silico study - Muhammad Sulaiman Daulai; Indah Wijayanti; Yuli Retnani; Suzuki Toshisada (Journal of Advanced Veterinary and Animal Research)
Objectives: This study aimed to assess the anti-methanogenic potential of Moringa oleifera L. phytogenic extracts through in silico inhibition of the methyl-coenzyme M reductase (MCR) receptor. Materials and Methods: Phytochemicals from M. oleifera were screened and compared with anti-methanogenic compounds such as 3-nitrooxypropanol and native MCR enzyme ligands (coenzyme M and coenzyme B). Molecular docking analysis was performed using AutoDock Vina on PyRx 0.8, and interactions were visualized with Discovery Studio 2024. Results: Selected phytochemicals, including pterygospermin, exhibited promising drug-likeness based on Lipinski's rule of five and absorption, distribution, metabolism, excretion, and toxicology properties. Pterygospermin demonstrated the highest binding affinity to the MCR enzyme's active site, with interactions including Pi-sulfur (Phe443), Pi-alkyl (Val482, Leu320, and Met324), Pi-Pi stacking (Phe330), and van der Waals forces (Tyr333 and Ser325). Conclusion: Pterygospermin shows potential as a competitive inhibitor of the MCR enzyme, providing a sustainable approach to mitigate methane emissions in livestock and contribute to global greenhouse gas reduction efforts. [J Adv Vet Anim Res 2025; 12(2.000): 361-373]